Differential Expression of Host Biomarkers in Saliva and Serum Samples from Individuals with Suspected Pulmonary Tuberculosis - Phalane, Khutso G.; Kriel, Magdalena; Loxton, Andre G.; Menezes, Angela; Stanley, Kim; van der Spuy, Gian D.; Walzl, Gerhard; Chegou, Novel N. (Mediators of Inflammation, 2013)
The diagnosis of tuberculosis remains challenging in individuals with difficulty in providing good quality sputum samples such as children. Host biosignatures of inflammatory markers may be valuable in such cases, especially if they are based on more easily obtainable samples such as saliva. To explore the potential of saliva as an alternative sample in tuberculosis diagnostic/biomarker investigations, we evaluated the levels of 33 host markers in saliva samples from individuals presenting with pulmonary tuberculosis symptoms and compared them to those obtained in serum. Of the 38 individuals included in the study, tuberculosis disease was confirmed in 11 (28.9%) by sputum culture. In both the tuberculosis cases and noncases, the levels of most markers were above the minimum detectable limit in both sample types, but there was no consistent pattern regarding the ratio of markers in serum/saliva. Fractalkine, IL-17, IL-6, IL-9, MIP-1β, CRP, VEGF, and IL-5 levels in saliva and IL-6, IL-2, SAP, and SAA levels in serum were significantly higher in tuberculosis patients (P<0.05). These preliminary data indicate that there are significant differences in the levels of host markers expressed in saliva in comparison to those expressed in serum and that inflammatory markers in both sample types are potential diagnostic candidates for tuberculosis disease.